Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.15407/mfint.41.10.1315
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of a New Ti–1.5Al–1Fe–7.2Cr Alloy Produced with Conventional Cast and Wrought Approach

Abstract: The ability to obtain a new cost-efficient titanium β-metastable alloy Ti-1.5 (%wt.)Al-1Fe-7.2Cr using conventional cast and wrought technological approaches is investigated. The microstructure and phase composition are characterized in the as-cast, hot-deformed and aged states. The aging behaviour of the state water-quenched from the temperature of single-phase β-field alloy is studied by exposure at 673 K and 773 K, and compared with previously obtained data for the Ti-11V-7Cr-4Al alloy. The mechanical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…As the amount of Mo addition increased, the electrical resistivity and electrical resistance decreased, and the HV increased. A comparison between the Ti-Mo and Ti-Fe alloys suggests that this trend is reasonabl 5,6) . Furthermore, in all cases, the electrical resistance showed a negative temperature dependence.…”
Section: Stq Statementioning
confidence: 96%
“…As the amount of Mo addition increased, the electrical resistivity and electrical resistance decreased, and the HV increased. A comparison between the Ti-Mo and Ti-Fe alloys suggests that this trend is reasonabl 5,6) . Furthermore, in all cases, the electrical resistance showed a negative temperature dependence.…”
Section: Stq Statementioning
confidence: 96%
“…2b). The regimes of subsequent thermomechanical processing and heat treatments were chosen basing on the technological approaches developed in [16,[22][23][24]. Machined semiproducts were subjected to 3D pressing at initial temperature of 1100 °C (Fig.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…The results of tensile tests of all program materials are presented in Table 5. Data for the Ti-1.5Al-1Fe-7.2Cr alloy (lines 17-19) with somewhat higher chromium content [23,24] were added for comparison to illustrate the influence of C Mo above 10 wt.%. Typical examples of engineering tensile stress-strain curves for alloys #3 and #4 are given in Fig.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…The addition of aluminum in Ni-Ti alloy researched by Pavel Salvetr et al showed the decrease of porosity and improvement of corrosion resistance and hardness [33]. Aluminum (Al) addition is due to its distinctive characteristics, such as low density (2.7 g/cm 3 ) and combination of moderate strength and high ductility, thermal conductivity, electric conductivity, corrosion-resistance [34,35].…”
Section: Introductionmentioning
confidence: 99%